Modulating effect of vitamin D status on serum anti-adenovirus 36 antibody amount in children with obesity: National Food and Nutrition Surveillance - Bahareh Nikooyeh; Bruce W. Hollis; Tirang R. Neyestani (BMC, 2020)
Abstract Background The association of ADV-36 infection and obesity has been reported in children. The objective of this study was to examine the hypothesis that the association between ADV-36 infection and adiposity may be mediated by sub-optimal vitamin D status of the host. Methods Ninety one apparently healthy children in different weight categories (normal weight: 33, overweight: 33, obesity: 25) aged 5-18 years were randomly selected from the registered population at National Food and Nutrition Surveillance Program (NFNS). The groups were matched based on age and sex. Anthropometric, biochemical and serological assessments were performed. Results The amount of anti-ADV36-Ab increased whereas circulating concentrations of 25(OH) D decreased across BMI categories with higher amounts in children with normal weight than in children with overweight and obesity (31.0 ± 16.4, 22.5 ± 10.5 and 21.9 ± 9.8 nmol/L, respectively, p = 0.004). Logistic regression analysis revealed that for each unit increment of anti-ADV36-Ab, the chance of increase in weight was 8.5 times (OR: 8.5, p = 0.029). Interestingly, when 25(OH) D was introduced into the model, anti-ADV36-Ab was no longer the predictor of weight increment and the chance of increase in weight reduced 5% for each unit increase in 25(OH) D concentration (OR: 0.95, p = 0.012). Conclusion It is suggested that ADV36-induced lipogenesis may be mediated by vitamin D deficiency in children with obesity.